Herança de resistência: terreiros e comunas na pauliceia desvairada... e o samba continua - Jesus, Edson Roberto de (2017)
Since the last decade of the twentieth century, the City of São Paulo has witnessed the emergence of a variety of groupings - Terreiros and Comunidades - that have the Samba and Roda de Samba - black and popular cultural expression - as central elements activities and existence. This research aims to understand how these places of a cultural practice that provides situations and moments of leisure and entertainment, but also moments of reflection on the reality in which this cultural practice and its practitioners, adepts and lovers are inserted, constitute as places of rescuing and promoting Samba's memory and tradition, of re-signification of space, establishment of community and identity ties, in a full exercise of citizenship and in a continuous action of cultural resistance and continuation of cultural practices whose common denominators refer to the actions undertaken by the population in the early twentieth century